The unconventional monetary policy of the ECB and the international economic and financial crisis: effectiveness versus exhaustion - Mendonça, António (2022)
On 10 March 2016 the ECB took the historic decision to reduce the interest rate on the main refinancing operations of the Euro system by five basis points to 0 %. In line with this, it reduced the rate on the marginal lending facility to 0.25 % (previously 0.3 %) and the rate on permanent deposit facility by ten basis points, to −0.4 %. This opened a new phase of unconventional monetary policy use. In this essay we will discuss the issue of the effectiveness versus the exhaustion of monetary policy followed by the ECB in response to the Eurozone effects of global economic and financial crisis. We firstly discuss the nature and justifications for the use of unconventional policy measures in the context of the crisis developments. We concentrate, in particular, on two central issues to understand the limits of monetary policy effectiveness, the so-called liquidity trap and the endogeneity versus exogeneity issue of money creation. Secondly, we provide some additional considerations on the relationship between the decreasing effectiveness of monetary policy and the increasing use of unconventional measures, seeking also to understand the differences between the stances of the ECB and the US Fed. Finally, we discuss the contradictions between the fiscal and monetary policies stances as a booster factor in exhausting the effect of the monetary policy, and conclude by affirming the absolute need to reform the Euro system.